Dentigerous Cyst Associated with Unusual Supernumerary Teeth: A Case Report - Sharma, Amita; Singh, Varun Pratap; Sharma, Sonam (Asian Journal of Medical Sciences, 2011)
Dentigerous cyst is a developmental odontogenic cyst associated with unerupted teeth, odontomes or supernumerary teeth. About 95% of dentigerous cysts involve the permanent dentition and only 5% are associated with supernumerary teeth. Supernumerary teeth should be examined very carefully to prevent possible effects on adjacent regular teeth and possible cystic development . Dentigerous cysts are usually slow-growing lesions and may attain a considerable size with minimal or no symptoms. Ameloblastoma, mucoepidermoid carcinoma, and squamous cell carcinoma have also been reported to arise from the lining epithelium of dentigerous cysts, indicating the pluripotentiality of their cells. Early detection and removal of such cysts is therefore important to reduce potential morbidity. A rare case of a twelve year old boy with two supernumerary teeth, of which one was associated with dentigerous cyst is described here along with the treatment strategy employed for the patient. Key Words: Dentigerous cyst; Supernumerary tooth; Mesiodens; Molariform; Tuberculate; Conical DOI: http://dx.doi.org/10.3126/ajms.v2i2.4247 Asian Journal of Medical Sciences 2 (2011) 124-127